2016
DOI: 10.1080/17425247.2016.1193154
|View full text |Cite
|
Sign up to set email alerts
|

Potential benefits of chewing gum for the delivery of oral therapeutics and its possible role in oral healthcare

Abstract: Evidence for oral-health benefits of chewing gum additives is hard to obtain due to their relatively low concentrations and rapid wash-out. Clinical effects of gum additives are overshadowed by effects of increased mastication and salivation due to the chewing of gum and require daily chewing of gum for prolonged periods of time. Future studies on active ingredients should focus on specifically targeting pathogenic bacteria, whilst leaving the healthy microbiome unaffected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 111 publications
(123 reference statements)
0
32
0
1
Order By: Relevance
“…[138,139] Currently, marketed products of chewing gum contain chlorhexidine as an antiplaque agent (e.g. Recent evidence has indicated that chewing gum is an interesting and promising carrier for antiplaque agents, due to its longer residence time in the mouth than toothpaste or rinses.…”
Section: Other Systemsmentioning
confidence: 99%
“…[138,139] Currently, marketed products of chewing gum contain chlorhexidine as an antiplaque agent (e.g. Recent evidence has indicated that chewing gum is an interesting and promising carrier for antiplaque agents, due to its longer residence time in the mouth than toothpaste or rinses.…”
Section: Other Systemsmentioning
confidence: 99%
“…Indeed, one of the goals of oral hygiene is to reduce the amount of pathogenic bacteria, shifting the oral microbiome towards a less pathogenic one. [13,53] In this regard, active substances contained in the mouthrinses should ideally act progressively, with a gradual change in the composition of the oral biofilm. [13] One possible approach is the use of mouthrinses with antibacterial compounds which inhibit pathogenic bacteria and maintain bacteria associated with a healthy microbiota.…”
Section: Expert Opinionmentioning
confidence: 99%
“…[13,53] In this regard, active substances contained in the mouthrinses should ideally act progressively, with a gradual change in the composition of the oral biofilm. [13] One possible approach is the use of mouthrinses with antibacterial compounds which inhibit pathogenic bacteria and maintain bacteria associated with a healthy microbiota. [2,13] Among the various candidate molecules, HA and triclosan demonstrate the most promise.…”
Section: Expert Opinionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sus principales agentes patógenos son el Streptococcus mutans (S. mutans) y Porphyromonas gingivalis (P. gingivalis) (2,3) . Para mantener la salud de los tejidos bucales se requieren de cepillos dentales, dentífricos, hilo dental y antisépticos bucales (4)(5)(6) . El gluconato de clorhexidina (CHX) es la primera elección (7) , porque conjuga los efectos antibiopelícula/antibacteriano.…”
Section: Mensajes Clave Introducciónunclassified